Oblomok imperii - Ermler, Fridrikh (Soviet Union : Sovkino, 1929)
The main hero, lieutenant Filimonov, loses his memory during WWI. He regains it accidentally 10 years later, and he takes off to find his home and his wife. To his surprise, he does not find any familiar sights or faces, discovering instead a new life in the 'city of Lenin'. Gradually he learns about the meaning of the changes and becomes an enthusiastic worker at the nationalized factory.
Keywords: Fiction films